Management practices affecting helminthiasis in goats - Abdul Aziz, Nor Azlina; Abdullah Sani, Rehana; Omar, Mohamed Ariff (Universiti Putra Malaysia Press, 2011)
The study was conducted to investigate the effects selected management practices have on worm burden in goats as reflected by faecal egg counts. The faecal examination of six goat farms for the quantitative presence of strongyles was conducted in Terengganu. A questionnaire was developed and directed to six farmers on the management practices adopted on their farms. The management practices selected in the study were grazing time, mineral block supplementation, type of drug used, breed, and source of animal, grass type, additional feed, and drenching personnel. The data analysis was done through systematic approaches using t-test, Spearman correlation and ANOVA. Afternoon grazing reduced the mean FEC nearly five-fold compared to morning grazing and mineral block supplementation reduced FEC two-fold compared to unsupplemented goats (P<0.05).